2019
DOI: 10.1016/j.jcmgh.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Mist1 Expression Is Required for Paneth Cell Maturation

Abstract: BackgroundPaneth cells are professional secretory cells found within the small intestinal crypt epithelium. Although their role as part of the innate immune complex providing antimicrobial secretory products is well-known, the mechanisms that control secretory capacity are not well-understood. MIST1 is a scaling factor that is thought to control secretory capacity of exocrine cells.MethodsMist1+/+ and Mist1–/– mice were used to evaluate the function of MIST1 in small intestinal Paneth cells. We used histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Another growth factor named helix-loop-helix transcription factor (MIST1) is a scaling factor; this factor can control the fate of exocrine cells (such as pancreatic acinar cells, zymogenic cells of the stomach) to affect secretory capacity [105]. In the small intestine, the absence of MIST1 increased the numbers of PCs, which exhibit an LYZ/ MUC2+ intermediate cell phenotype and morphologically show immature features, including decreased granule size and distended rough endoplasmic reticulum [105,106] (Fig. 3).…”
Section: Growth Factor-mediated Signalling Pathways Regulate the Devementioning
confidence: 99%
“…Another growth factor named helix-loop-helix transcription factor (MIST1) is a scaling factor; this factor can control the fate of exocrine cells (such as pancreatic acinar cells, zymogenic cells of the stomach) to affect secretory capacity [105]. In the small intestine, the absence of MIST1 increased the numbers of PCs, which exhibit an LYZ/ MUC2+ intermediate cell phenotype and morphologically show immature features, including decreased granule size and distended rough endoplasmic reticulum [105,106] (Fig. 3).…”
Section: Growth Factor-mediated Signalling Pathways Regulate the Devementioning
confidence: 99%
“…We showed that genes regulated downstream of XBP1 are modulated as disease progresses in SAMP1/YitFc mice. For example, levels of two ER stress makers, GRP78 and calreticulin, increase, and levels of MIST1, which inhibits ER stress (42), decrease, suggesting that pathophysiology in SAMP1/YitFc mice shares certain pathways with CD patients. In addition, environmental risk factors of CD such as high-fat diet (23) and zinc deficiency (62) induce ER stress in Paneth cells (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…In SAMP1/YitFc mice at 20 wk, the expression of both GRP78 and calreticulin was remarkably increased in abnormal Paneth cells, in contrast to low expression in ICR mice (Fig S5A and B). Furthermore, we analyzed expression of transcription factor, MIST1, which is known to suppress ER stress and is specifically expressed in Paneth cells of the intestinal epithelium (42). By immunofluorescent staining, MIST1 was strongly expressed in the nucleus of Paneth cells in 20-wk ICR mice.…”
Section: Abnormal Paneth Cells Exhibit Er Stressmentioning
confidence: 99%
“…Their secretory function depends on induction and maintenance of subcellular secretory architecture via unknown mechanisms. In this issue of Cellular and Molecular Gastroenterology and Hepatology , Dekaney et al 1 show that the basic helix-loop-helix Class A basic helix-loop-helix protien 15 (BHLHA15)/Muscle, Intestine, and Stomach expression 1 (MIST1) (BHLHA15) helps govern secretory function in Paneth cells.…”
mentioning
confidence: 99%
“…In this issue of Cellular and Molecular Gastroenterology and Hepatology , Dekaney et al 1 make important steps toward increasing our understanding of Paneth and intermediate cells. Similar to pancreatic acinar and gastric chief cells, Paneth cells have long lifespans and elaborate exocrine secretory machinery.…”
mentioning
confidence: 99%